THE RELETIONSHIP OF CHILDRENS KNOWLEDGE ABOUT FOOD TYPES WITH DENTAL CARE IN SMP NEGERI 1 PEUKAN BADA KABUPATEN ACEH BESAR - Wilis, Ratna; Wirza, Wirza (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2019)
Background: Test results and initial interviews by the investigators of the 30 students of SMPN 1Peukan Bada, Aceh Besar gained an average of DMF-T / def-t reaches 2.02 (low category), the lower knowledgeable about the types of snacks were 12 pupils (40%) and the high knowledgeable about the types of snacks were 18 pupils (60%). This study aims to determine the relationship of knowledge about the types of snacks children with dental caries in the SMPN 1 students Peukan Bada, Aceh Besar. Methods: This study was analytical, The population in this study were all students at SMPN 1 Peukan Bada many as 372 students. Sampling by using proportional sampling is numbered 79 students. Results: The results showed that students who have a high knowledge with caries criteria were numbered 17 people (29.8%). Statistical test results obtained p value of 0.196, while Î± = 0.05 and df = 4. Therefore p> Î±, so that Ha rejected, there is no relationship of knowledge about the types of snacks children with dental caries in students SMPN 1Peukan Bada, Aceh Besar. Conclusion: No relationship of knowledge about the types of snacks children with dental caries in the SMPN 1 Peukan Bada, Aceh Besar district.